Difficulty and reasons for sustainable roadway design – the case from Taiwan - Chang, Andrew S.; Tsai, Calista Y. (Journal of Civil Engineering and Management, 2015)
To accomplish sustainable design, it is essential to understand its barriers or limitations. This study investigated difficulties and their reasons for sustainable design using roadways as an example. A checklist of 60 sustainability items for roadway design was used to interview roadway designers to identify levels of difficulty, reasons for difficulty and proportions of difficulty reasons when designing these sustainability items. The results were analyzed and compared among sustainable items and design work. The difficulties of incorporating sustainability into designs are classified into three levels as compared with conventional design: equal, medium and high. The average difficulty for sustainable roadway design is between low and medium level; 28 of the 60 items were found to be at the same level of difficulty as conventional design. The technical items are regarded more difficult to adopt than material items. Nine reasons were identified for sustainable roadway design difficulty in which four are in the pre-design stage and five are in the design stage. The proportions of difficulty reasons in the pre-design and design stages are 63% and 37%, respectively. This implies that more difficulties will be encountered in the pre-design stage, and the designers can try to overcome or reduce difficulty in design stage. The top three reasons are natural preconditions; criteria and specifications; and owner, policy and law, which cause 33%, 20% and 14% of the difficulty, respectively. This study pointed out the difficulties and reasons for sustainable roadway design. Having a comprehensive understanding of the difficulties allows a designer to more accurately determine potential limitation, and to make better choices as to which sustainable items a particular construction project should pursue.